Improving Access to Accommodations: Reducing Political and Institutional Barriers for Canadian Postsecondary Students with Visual Impairments. (January 2016) - Ostrowski, Christopher P.
Challenges to obtaining quality academic accommodations for students with visual impairments in postsecondary education hinder accessibility and the success of such students. The limitations of current policies and practices intended to address the needs of students in Canada are examined and potential solutions are discussed. Further systemic changes are needed to improve the quality and timeliness of accommodations.